Computational fluid dynamics applied to competitive swimming: the role of finger position - Marinho, D.A. (2010)
The best fingers’ relative position during the underwater path of the stroke cycle in swimming seems to be an unclear issue. Even in elite level swimmers, different relative positions of thumb and finger spreading can be observed. The aim of the current abstract was to present the hydrodynamic characteristics of a true model of a swimmer’s hand with different fingers’ positions using computational CFD.